2012
DOI: 10.1098/rsta.2012.0098
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of H + –H 2 collision complexes between 11 and 28K

Abstract: Formation of via association of H + with H 2 has been studied at low temperatures using a 22-pole radiofrequency trap. Operating at hydrogen number densities from 10 11 to 10 14  cm −3 , the contributions of radiative, k r , and ternary, k 3 , association have been extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Moreover, at low temperatures, H 2 molecules also act as a buffer gas because of the low probability for a reactive collision. Recent experiments in our apparatus (Plašil et al 2012;Zymak et al 2013) as well as in other 22-pole trap experiments have confirmed that the collisional temperature is slightly higher than the temperature of the trap. In the present case we can safely assume that the collisional temperature in interaction of OD − with H 2 does not exceed the trap temperature by more than 10 K. For simplicity of presentation, we define the collisional temperature as T = T 22PT + 5 K with an uncertainty of ±5 K.…”
Section: Methodsmentioning
confidence: 72%
“…Moreover, at low temperatures, H 2 molecules also act as a buffer gas because of the low probability for a reactive collision. Recent experiments in our apparatus (Plašil et al 2012;Zymak et al 2013) as well as in other 22-pole trap experiments have confirmed that the collisional temperature is slightly higher than the temperature of the trap. In the present case we can safely assume that the collisional temperature in interaction of OD − with H 2 does not exceed the trap temperature by more than 10 K. For simplicity of presentation, we define the collisional temperature as T = T 22PT + 5 K with an uncertainty of ±5 K.…”
Section: Methodsmentioning
confidence: 72%
“…14 The observed resonances observed here and for the scattering reactions for the H + 3 system 4 can be directly related with H + −H 2 radiative association processes. 44,60 In recent experimental radio frequency ion trap investigations, the deviations from the expected statistical behaviour were tentatively attributed to the rather low number of states accessible to the H + 3 complex at the temperature regime (11 K-33 K) considered there. In order to elucidate the issue more QM calculations on sufficiently precise PESs are required.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The apparent success of the statistical treatments for this system has been also questioned by recent experimental work in which binary rate coefficients were measured for the stabilization of H + −H 2 collision complexes by means of a radio frequency ion trap at a temperature between T = 11 K and 33 K. The observed behaviour of the rate coefficients for both j = 0 and j = 1 initial rotational states for H 2 manifested differences with respect to the expected results from models designed on statistical assumptions for the association to form and stabilize H + 3 complexes. 44 The above mentioned SQM approach was also employed for the D + +H 2 reaction on Ref. 45 besides TDWP calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Energy scaling of TBR in charged gases was studied at temperatures down to a few K, especially for hydrogen and helium due to their relevance in plasmas and astrophysics (e.g. [5,6]). Depending on the studied temperature range a variety of power laws was found but not a common threshold law.…”
mentioning
confidence: 99%